2014
DOI: 10.1109/lgrs.2014.2311663
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Multitemporal SAR Image Filtering Based on the Change Detection Matrix

Abstract: 5 pagesInternational audienceThis letter presents an adaptive filtering approach of synthetic aperture radar (SAR) image times series based on the analysis of the temporal evolution. First, change detection matrices (CDMs) containing information on changed and unchanged pixels are constructed for each spatial position over the time series by implementing coefficient of variation (CV) cross tests. Afterwards, the CDM provides for each pixel in each image, an adaptive spatiotemporal neighborhood which is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 23 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Several recent studies perform change detection via different deep learning ideas [29]- [33]. [34] and [35] employ approaches based on probabilistic distributions for error terms and change detection matrices. [36] and [37] propose change detection methods based on clustering.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies perform change detection via different deep learning ideas [29]- [33]. [34] and [35] employ approaches based on probabilistic distributions for error terms and change detection matrices. [36] and [37] propose change detection methods based on clustering.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of speckle filtering approaches have been proposed for multi-temporal SAR images [11][12][13][14][15][16]. Multi-temporal PolSAR image speckle filtering is seldom studied independently.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-temporal filters operate in both the spatial and temporal dimensions, thus the reduction in resolution is not as likely to be as severe. Previous research has shown that multi-temporal filtering is beneficial for several applications including monitoring of water intake volume in small reservoirs (Amitrano et al 2014), agriculture (Caves et al 2011), SAR classification (Bruzzone et al 2004;Hachicha et al 2011) and SAR change detection (Lê et al 2014). Multi-temporal filtering effectiveness is determined by the number of images in the stack and the size of the filtering window.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-temporal filtering effectiveness is determined by the number of images in the stack and the size of the filtering window. There are many different multi-temporal filters which have been developed (Chierchia et al 2017;Deledalle et al 2019;Gineste 1999;Lê et al 2014;Su et al 2014;Yuan et al 2018;Zhao et al 2018). At the time of this analysis, only the GAMMA multi-temporal filter and the Multitemporal Lee filter were available in the GAMMA software, which was used to process the RADARSAT-2 imagery.…”
Section: Introductionmentioning
confidence: 99%